Generalized Turan-Type Inequalities for the \((q,k)\)-Polygamma Functions - Nantomah, Kwara (Communications in Mathematics and Applications, 2018)
This study provides generalizations of the results of Merovci concerning some Turan-type inequalities involving the \((q,k)\)-Polygamma functions.
Keywords: \((q; k)\)-Polygamma function; Generalized Hölder's inequality; Generalized Minkowski's inequality; Weighted AM-GM inequality